Perception of post-stroke patients on case management conducted by nurses - Souza, Pollyanna Bahls de; Mantovani, Maria de Fátima; Silva, Ângela Taís Mattei da; Paz, Vanêssa Piccinin (Revista da Escola de Enfermagem da USP, 2021)
Objective: To identify the perception of post-stroke patients on the case management conducted by nurses. Method: Qualitative descriptive study with 13 post-stroke patients, followed-up with case management conducted by a nurse for six months, and interviewed at home one month after the end of the follow-up. The interviews were recorded, transcribed in full and analyzed with the help of a software. Results: Of the 13 participants, 57.14% were men and 50% were between 50 and 59 years. Content analysis resulted in three categories: “Self-management of care”, which addressed changes in attitudes towards treatment, mainly due to concern of recurrence in a short period of time; “Sequelae and late repercussions of the stroke”, which presents participants’ difficulties after the event; and “Support received after a stroke”, which emphasizes the actions and attitudes of the case manager nurse during the follow-up period. Conclusion: Case management was perceived by the participant as a health-promoting tool capable of increasing treatment adherence.